2022
DOI: 10.1096/fj.202101663r
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the class IIa histone deacetylases substrate specificity

Abstract: Class IIa histone deacetylases (HDACs) play critical roles in vertebrate development and physiology, yet direct evidence of their intrinsic deacetylase activity and on substrate specificity regarding the peptide sequence is still missing. In this study, we designed and synthesized a combinatorial peptide library allowing us to profile class IIa HDACs sequence specificity at positions +3 through −3 from the central lysine modified by the well‐accepted trifluoroacetyl function. Our data revealed a strong prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Moreover, the kinetic effects of the interactions varied widely between KDAC6 and KDAC8, indicating that the specific interactions of each KDAC have distinct effects not predicted by a purely sequence-based substrate analysis. Recently reported work characterizing the preferences of KDACs 4, 5, 7, and 9 also found a strong preference for these residues, as well as phenylalanine, and it seems likely that these KDACs will also eventually prove to have a characteristic interaction surface . Glutamic acid was disfavored by both KDAC8 and KDAC1, but only by KDAC8 in both positions.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, the kinetic effects of the interactions varied widely between KDAC6 and KDAC8, indicating that the specific interactions of each KDAC have distinct effects not predicted by a purely sequence-based substrate analysis. Recently reported work characterizing the preferences of KDACs 4, 5, 7, and 9 also found a strong preference for these residues, as well as phenylalanine, and it seems likely that these KDACs will also eventually prove to have a characteristic interaction surface . Glutamic acid was disfavored by both KDAC8 and KDAC1, but only by KDAC8 in both positions.…”
Section: Discussionmentioning
confidence: 94%
“…Recently reported work characterizing the preferences of KDACs 4, 5, 7, and 9 also found a strong preference for these residues, as well as phenylalanine, and it seems likely that these KDACs will also eventually prove to have a characteristic interaction surface. 74 Glutamic acid was disfavored by both KDAC8 and KDAC1, but only by KDAC8 in both positions. The effect of arginine differed greatly between the three, as it had a negative effect on the activity for KDAC6, no significant effect for KDAC8, and different effects on KDAC1 activity depending on its position.…”
Section: Discussionmentioning
confidence: 96%
“…Recent substrate specificity studies of several HDACs indicate that substrate residues immediately preceding (−1) or following (+1) the acetyllysine are most sensitive to substrate recognition and the effect of −3/‐2 or +3/+2 residues is rather milder [20,21] . Thus, substitution of amino acid residues further away from acetyllysine is unlikely to have significant impact on HDAC activity.…”
Section: Resultsmentioning
confidence: 99%
“…Recent substrate specificity studies of several HDACs indicate that substrate residues immediately preceding (À 1) or following (+ 1) the acetyllysine are most sensitive to substrate recognition and the effect of À 3/-2 or + 3/ + 2 residues is rather milder. [20,21] Thus, substitution of amino acid residues further away from acetyllysine is unlikely to have significant impact on HDAC activity. Inspection of the human H2B sequence revealed that a LPKTG motif recognized by wild type SrtA may be introduced in the N-terminal region of H2B by substituting Ala-9 (+ 4 residue) to Leu and Lys-12 (+ 7 residue) to Thr respectively (Figure 1a).…”
Section: Semisynthesis Of H2bk5acmentioning
confidence: 99%
“…For example, class IIa HDACs (HDAC4, HDAC5, and HDAC7) shuttle between the nucleus and the cytoplasm [ 87 ]. HDAC4 recognizes a variety of extra-nuclear proteins as substrates, including forkhead transcription factors of the O class (FOXO), myosin heavy chain isoforms (MyHC), PGC-1α, and heat shock cognate 71 kDa (Hsc70) [ 88 ].…”
Section: Interaction Between αS and Epigenetic Factorsmentioning
confidence: 99%